Doppler Analysis of Forward Scattering Radar With Opportunistic Signals From LEO Satellites - Defeng Huang (IEEE Access, 2022)
Recently microwave communication signals from low Earth orbit (LEO) satellites have been proposed to be used to detect flying objects in a ground-based forward scattering passive radar setup. In this work the Doppler shift and the Doppler spread due to the flying object in such a system are derived directly from the Fresnel-Kirchhoff diffraction formula using a rotational Cartesian coordinate system to accommodate the continuously moving signal source from the LEO satellites. Coordinate transformations for flying objects including those in the atmosphere with rectilinear motion relative to the ground and those in space with circular orbits are investigated. Both analytical and simulation results demonstrate that the Doppler shift and Doppler spread are related to the velocity and volumetric profile of the flying object, thereby in future they may be used to help identify its size and velocity.